Stromal cell diversity associated with immune evasion in human triple‐negative breast cancer - Wu, Sunny Z; Roden, Daniel L; Wang, Chenfei; Holliday, Holly; Harvey, Kate; Cazet, Aurélie S; Murphy, Kendelle J; Pereira, Brooke; Al‐Eryani, Ghamdan; Bartonicek, Nenad; Hou, Rui; Torpy, James R; et al. (The EMBO journal, 2020)
The tumour stroma regulates nearly all stages of carcinogenesis. Stromal heterogeneity in human triple‐negative breast cancers (TNBCs) remains poorly understood, limiting the development of stromal‐targeted therapies. Single‐cell RNA sequencing of five TNBCs revealed two cancer‐associated fibroblast (CAF) and two perivascular‐like (PVL) subpopulations. CAFs clustered into two states: the first with features of myofibroblasts and the second characterised by high expression of growth factors and immunomodulatory molecules. PVL cells clustered into two states consistent with a differentiated and immature phenotype. We showed that these stromal states have distinct morphologies, spatial relationships and functional properties in regulating the extracellular matrix. Using cell signalling predictions, we provide evidence that stromal‐immune crosstalk acts via a diverse array of immunoregulatory molecules. Importantly, the investigation of gene signatures from inflammatory‐CAFs and differentiated‐PVL cells in independent TNBC patient cohorts revealed strong associations with cytotoxic T‐cell dysfunction and exclusion, respectively. Such insights present promising candidates to further investigate for new therapeutic strategies in the treatment of TNBCs. Synopsis This single‐cell gene expression resource deciphers the composition of triple‐negative breast cancer (TNBC) stroma, revealing distinct subclasses of cancer‐associated fibroblasts (CAFs) and perivascular‐like (PVL) cells. These signatures are informative on tumour aetiology and potential strategies for development of targeted therapies. Single‐cell analysis of primary TNBC highlights clusters of stromal and immune cell types. TNBC stroma is comprised of myofibroblast‐like CAFs, inflammatory‐like CAFs, differentiated PVL and immature PVL cells. Stromal subclasses differ in surface markers, spatial localisation in tissue, ECM functions, and predicted cellular crosstalk with immune cells. Inflammatory‐like CAF and differentiated PVL cells are associated with cytotoxic T‐cell dysfunction and exclusion in independent TNBC‐patient cohorts. Graphical Abstract Single‐cell profiling of primary breast cancer provides unprecedented insights into cell‐type heterogeneity within the tumor microenvironment.